Pengaruh Tata Kelola Perusahaan dan Kredit Bermasalah pada Harga Saham Bank BUMN dengan Profitabilitas sebagai Vatiabel Intervening - A Nasrullah (Sekolah Pascasarjana Perbanas Jakarta, 2020)
The study analyzes the effect of corporate governance and non-performing loans on bank stock prices with profitability as an intervening variable. The population in this study is the BUMN Bank in Indonesia (BRI, BNI, BTN, Mandiri) using financial statement data in 2010-2018. This study analyzes the influence of corporate governance, non-performing loans and profitability on BUMN Bank's financial performance. By using a quantitative approach and the SmartPLS version 3.0 program as an analysis tool. The results show that GCG has a positive and significant effect on ROA. GCG also has a positive and significant effect on shares, and NPL has a positive and significant effect on ROA. NPL has a positive and significant effect on stocks, ROA has a positive and significant effect on shares, GCG is positive and significant on shares is intervened by ROA, and NPL has a positive and significant effect on shares intervened by ROA. The study suggests that deepening observations provide evidence that composite values of GCG, NPL, and ROA are interrelated. When a bank implements good corporate governance, improving credit risk management is a necessity.